Why buildings collapse in the earthquakes, Turkey case (International Journal of Engineering and Computer Science, 2020)
Many European countries with shores to the Mediterranean are under earthquake risk. Earthquakes in Turkey in the last 50 years caused lost of more than 50,000 human lives. Reinforced concrete buildings can collapse and cause loss of life even in earthquakes smaller than the design earthquakes defined by the seismic code. In this study, housing construction system and earthquake-resistant buildings in terms of system production problems in Turkey were discussed. The most common damage types after earthquakes are summarized.